(untitled) (LIS TODAY, 2024)
The study presents the webometric analysis of the websites of 7 Central Universities of the Eastern India region. The study aims to identify and evaluate the web presence, domain name, Domain Authority, Page Authority, Google PageRank, Rich files, Language, and Social Media presence of the selected websites under study. To accomplish the objectives of the study, the Google search engine, some search engine optimization (SEO) tools, and manual website visits have been used to analyse the websites under study. Major findings of the study include that all universities’ websites have the same Google PageRank value i.e. 4, the website of Visva Bharti has the highest Domain Authority, Central University of Jharkhand’s website has the highest Page Authority, the website of Nalanda University is the single website which uses only one language, i.e. English. All universities have their presence on social media at different platforms. The study is unique and latest in the website analysis category. Very few webometric studies have been conducted on the universities of the Eastern region of India. This study is an effort to fill this gap. The present study concluded with some suggestions that will be helpful for Policy-makers and Website developers to enhance their websites and their visibility on the Web.